2003
DOI: 10.1111/j.0022-3646.2003.03906001_132.x
|View full text |Cite
|
Sign up to set email alerts
|

132 
Parasites and Phytoplankton, with a Special Emphasis on Dinoflagellate Infections

Abstract: ABSTRACT. Planktonic members of most algal groups are known to harbor intracellular symbionts, including viruses, bacteria, fungi, and protozoa. Among the dinoflagellates, viral and bacterial associations were recognized a quarter century ago, yet their impact on host populations remains largely unresolved. By contrast, fungal and protozoan infections of dinoflagellates are well documented and generally viewed as playing major roles in host population dynamics. Our understanding of fungal parasites is largely … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
101
0

Year Published

2008
2008
2015
2015

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(107 citation statements)
references
References 18 publications
6
101
0
Order By: Relevance
“…Regardless, the presence of the RC-Rep gene in the genome of PgV-12T lends additional support to the hypothesis that unicellular algae may host at least some of the CHIVs. More generally, parasitic and symbiotic relationships involving unicellular algae are highly prevalent in aquatic environments 50 and might be central for the emergence of new virus types, such as CHIVs, by providing a unique environment accessible for viruses infecting phylogenetically distant hosts. Such co-localization of various genetic elements of distinct origins and histories could also explain the evolutionary relationships between RC-Reps of prokaryotic plasmids and eukaryotic ssDNA viruses 12,13,15,21,22 .…”
Section: 00mentioning
confidence: 99%
“…Regardless, the presence of the RC-Rep gene in the genome of PgV-12T lends additional support to the hypothesis that unicellular algae may host at least some of the CHIVs. More generally, parasitic and symbiotic relationships involving unicellular algae are highly prevalent in aquatic environments 50 and might be central for the emergence of new virus types, such as CHIVs, by providing a unique environment accessible for viruses infecting phylogenetically distant hosts. Such co-localization of various genetic elements of distinct origins and histories could also explain the evolutionary relationships between RC-Reps of prokaryotic plasmids and eukaryotic ssDNA viruses 12,13,15,21,22 .…”
Section: 00mentioning
confidence: 99%
“…It has recently been postulated that dinoflagellate blooms may also result from the absence of efficient pathogens in newly invaded areas (Salomon et al 2003), a theory known as the 'enemy release hypothesis' in terrestrial ecology (Keane & Crawley 2002). The major eukaryotic pathogens described for dinoflagellates are unicellular parasitoids belonging to the Phylum Alveolata (perkinsoids and Amoebophryidae; Park et al 2004). Both lineages ultimately kill their hosts to accomplish their life cycles (Park et al 2004), endowing these organisms with a typical parasitoid feature (i.e.…”
Section: Introductionmentioning
confidence: 99%
“…The major eukaryotic pathogens described for dinoflagellates are unicellular parasitoids belonging to the Phylum Alveolata (perkinsoids and Amoebophryidae; Park et al 2004). Both lineages ultimately kill their hosts to accomplish their life cycles (Park et al 2004), endowing these organisms with a typical parasitoid feature (i.e. parasitism is similar to predation by grazers in that a part of the host population will be killed).…”
Section: Introductionmentioning
confidence: 99%
“…Phylogenetic analysis has shown that Perkinsea are a deeply divergent sister-group of dinoflagellate alveolates (16). Only three representative groups of Perkinsea were previously described morphologically and taxonomically: Perkinsus spp., parasites of marine bivalves (e.g., oysters and clams), Parvilucifera spp., parasites of dinoflagellates, and Rastrimonas subtilis (previously Cryptophagus subtilis), parasites of cryptophyte algae (17)(18)(19)(20). However, environmental sequence Significance Amphibians are among the most threatened animal groups.…”
mentioning
confidence: 99%